Prognostic and Risk Factors in Patients with Locally Advanced Cutaneous Squamous Cell Carcinoma of the Trunk and Extremities - de Lima Vazquez Vinicius; Cristovam Scapulatempo; Natalia Martins Perpetuo; Faheez Mohamed; Teóclito Sachetto de Carvalho; Antônio Talvane Torres de Oliveira; José Getúlio Martins Segalla; André Lopes Carvalho (Journal of Skin Cancer)
55 patients with advanced cutaneous squamous cell carcinoma (CSCC) of the trunk and extremities were studied. A Tissue Microarray was constructed using immunohistochemistry to quantify expression of the HER family, E-cadherins, and podoplanin. Clinical and histopathological factors related to lymph node metastasis and prognosis were also established. Primary tumor positivity was 25.5% for EGFR, 87.3% for HER-3, and 48.1% for HER-4. Metastases were positive for EGFR in 41.7%, for HER-3 in 83.3%, and HER-4 in 43.5%. HER-2 was negative in all samples. Membrane E-cadherin and cytoplasmic E-cadherin were positive in 47.3% and 30.2% of primary tumors and 45.5% and 27.3% of metastases, respectively. Podoplanin was positive in 41.8% of primary tumors and 41.7% of metastases. Intratumoral lymphocytic infiltrate was associated with lymph node metastasis. Patients with T3 tumors had better cancer-specific survival (CSS) than those with T4 tumors; patients with no lymph node involvement had better CSS than patients with N1 tumors. Undifferentiated tumors and hyperexpression of podoplanin were negative prognostic indicators on multivariate analysis.